The Impact of Employee Stock Ownership Plan on the Cost of Equity Capital: Evidence from China. (29th November 2021) - Cheng, Fu; Ji, Shanshan
Abstract : Due to the immaturity of bond market and the defects of internal governance structure, Chinese-listed companies have a strong preference for equity financing. How to reduce the cost of equity capital is particularly important for Chinese-listed companies. As an equity incentive system, employee stock ownership plan (ESOP) can reduce the agency conflicts among shareholders, executives, and employees to some extent. These reduced conflicts will, in an efficient capital market, be reflected in a lower cost of equity capital. This paper investigates whether the implementation of ESOP in a new era in China affects the cost of equity capital and further explores whether the impact of ESOP on the cost of equity capital is affected by the ownership nature, the firm size, and the contract design of ESOP. The results show that the implementation of ESOP reduces the cost of equity capital of enterprises. Compared with state-owned enterprises and large enterprises, the implementation of ESOP is more likely to reduce the cost of equity capital in non-state-owned enterprises and small enterprises. Furthermore, the reduction effect of ESOP on the cost of equity capital is influenced by the contract design of ESOP. This study not only enriches the literature on the relationship between employee stock ownership and the cost of equity capital but also provides a new idea for listed companies to reduce the cost of equity financing.